War of the dragon - Jenkins, Jerry B.; Fabry, Chris, 1961-; LaHaye, Tim F. (Wheaton, Ill. : Tyndale House, 2003)
The Wisconsin hideout sends Vicki Byrne on a dangerous mission. In Israel, Judd Thompson and Lionel Washington wonder if they will survive as things go out of control, and in Petra, Sam Goldberg watches the approach of Global Community troops.
6.3
5-8
Keywords: Christian fiction; Christian life -- Fiction; Eschatology -- Fiction; Fantasy; Survival -- Fiction; Teenagers -- Fiction; Christian fiction; Christian life -- Fiction; Eschatology -- Fiction; Survival skills -- Fiction; Teenagers -- Fiction; Israel -- Fiction; Petra (Extinct city) -- Fiction; Wisconsin -- Fiction; Israel -- Fiction; Petra (Extinct city) -- Fiction; Wisconsin -- Fiction; Fantastic fiction